Effort Displayed During Appetitive Phase of Feeding Behavior Requires Infralimbic Cortex Activity and Histamine H1 Receptor Signaling - Riveros, María E.; Forray, María Ines; Torrealba, Fernando; Valdés, José L. (Frontiers in Neuroscience, 2019)
The chances to succeed in goal-directed behaviors, such as food or water-seeking, improves when the subject is in an increased arousal state. A high level of behavioral and vegetative excitation characterizes the appetitive phase of these motivated behaviors. The decision to engage and those particular behaviors and their organization depend on prefrontal cortical areas, such as the ventromedial prefrontal cortex. We propose that the infralimbic cortex (ILC) from the medial prefrontal cortex induces an increase in arousal, during the appetitive phase of motivated behavior, which is mediated by the activation of the brain histaminergic system. This increase in arousal results in higher motivation for getting foods rewards. To test this idea, we conduct a progressive ratio operant conditioning to test the degree of motivation for food, while the histaminergic system was pharmacologically manipulated. We found that the behavioral responses to obtain food, in hungry rats, were disrupted by inhibiting the infralimbic cortex trough muscimol infusion, blocking brain H1 histamine receptors by intracerebroventricular infusion of pyrilamine or by satiety. In contrast, the consummatory behavior was not affected by ILC inhibition. The extracellular histamine levels in the ILC increased in correlation with the degree of motivation measured in the progressive ratio test. ILC inhibition also disrupted this increase in histamine levels. The rise in extracellular histamine levels during the progressive ratio test was similar (ca. 200%) either during the active or the resting period of the day. However, the rising start from different basal levels. this suggests that the increase in histamine during this behavior is not simply due to the fact that animals are awake in their resting phase, but there is a motivation related release of histamine, suggestive of a specific form of brain activation. Serotonin another critical component of the Ascending Arousal System (AAS) was also tested, but not changes in the level of this neuromodulator was detected during the progressive ratio test. In conclusion, our results suggest that the ILC activation and the consequent increase in brain histamine release are necessaries for the normal performance of a motivated behavior such as feeding.